The Intersection of Max Planck’s Metaphysical Assertion and Christian Theology: A Pragmatic Review of Consciousness and Creation - R. Tjandrawinata, Raymond; B. Atawolo, Andreas (Green Publisher Indonesia, 2024)
This systematic review explores the intersection of Max Planck's assertion that